FORMATION OF PROFESSIONAL COMPETENCE IN MEDICAL STUDENTS: THE ROLE AND IMPORTANCE OF PEDAGOGY AND PSYCHOLOGY - Tajiboyeva Odinakhon,; Unarboyev Javlon, (TADQIQOTLAR, 2025)
Abstract:  This  article  provides  a  scientific  analysis  of  the  interrelation, integration, and significance of pedagogy and psychology in the process of developing professional  competence  among  medical  students  in  higher  medical  education institutions. It explores the essence and structure of professional competence, as well as the formation of empathy, reflection, and communication skills in the personality of a future physician.